Kontribusi Power Otot Lengan Terhadap Hasil Lempar Cakram Siswa SMA Negeri 1 Bangkinang Kabupaten Kampar - Rizki, Elfera; Permatasari, Vigi Indah; Azhari, Azhari (Jurnal Inovasi Olahraga, 2024)
Bentuk penelitian ini adalah penelitian korelasi dengan populasi seluruh siswa SMA Negeri 1 Bangkinang Kabupaten Kampar dengan jumlah populasinya sebanyak 20 orang. Sampel dalam penelitan ini didapat berdasarkan teknik total sampling. Sehingga semua populasi dijadi sampel yang berjumlah 20 orang. Instrument yang dilakukan dalam penelitian ini adalah tes power otot lengan dan tes hasil lempar cakram. Kemudian data diolah dengan statistik, dengan rumus korelasi product moment dan menggunakan rumus distribusi t untuk mengetahui signifikan atau tidak ada kontribusi pada taraf signifikan 0,05α. Hasil analisis data dalam penelitian ini diperoleh r sebesar 0,02 dengan besar kontribusinya ,04% ini tergolong kurang baik. Berdasarkan hasil penelitian yang dilakukan, maka dapat disimpulkan bahwa kurang terdapat kontribusi power otot lengan terhadap kemampuan hasil lempar cakram siswa SMA Negeri 1 Bangkinang Kabupaten Kampar. Dimana diperoleh r tabel = 0,02 < r hitung = 0,444 dengan kontribusi sebesar 0,04%. Kata kunci : Power otot lengan dan hasil lempar cakram ABSTRACT The problem in this research is at the time of the motion capture prefix students looked stiff in the throws this is due to lack of coordination of movements of the students, when throwing discs students always lose balance so that the disc is not directed straight at the time of throwing the disc that is released is not directed away things this is influenced by the strength of the arm muscles are not strong, and the lack of power of the students can be seen at the current pace menlempar not optimal. This research was conducted to determine whether there is an arm muscle power contribution to the results of throwing SMA Negeri 1 Bangkinang Kampar regency. Forms of this research is the correlation with the entire student population of SMA Negeri 1 Bangkinang Kampar district with population of 20 people. The sample in this research obtained by total sampling technique. So all dijadi population sample of 20 people. Instruments used in this research is to test the arm muscle power and test results discus throwing. Then the data is processed with statistical formula product moment correlation and using t distribution formula to determine the significant or no contribution to the significant level 0,05α. The results of data analysis in this study were obtained r of 0.02 with a major contribution, 04% is classified as poor.Based on the results of research conducted, it can be concluded that there is less power arm muscles contribute to the ability of the results of throwing SMA Negeri 1 Bangkinang Kampar regency. Where the table is obtained r = 0.02 <r count = 0.444 with a contribution of 0.04%. Keyword: Power Muscles In Your Arms and Throwing Results